Cellular detection of sst2A receptors in human gastrointestinal tissue. Issue 10 (10th September 2004) - Gugger, M; Waser, B; Kappeler, A; Schonbrunn, A; Reubi, J C
Abstract : Background and aim: Many neuroendocrine gastrointestinal tumours express receptors for the regulatory peptide somatostatin. Among the five existing somatostatin receptor (sst) subtypes, sst2A is the most frequently expressed in these tumours. However, little information is available about the cellular location of sst2A in corresponding non-neoplastic epithelial tissues. Methods: We searched for sst2A immunoreactive cells in non-neoplastic gastrointestinal tissues, and evaluated their number and immunohistochemical characteristics with neuroendocrine markers. Results: The gastric antrum showed numerous sst2A cells, situated in the epithelium, corresponding to gastrin containing neuroendocrine cells, while the gastric corpus was largely devoid of sst2A cells, including enterochromaffin-like cells. The remaining foregut, namely the duodenum and proximal jejunum, also contained a large number of sst2A cells, all being neuroendocrine cells and many of them characterised as gastrin cells. Sst2A cells were also detected in the midgut, in low numbers in the epithelium of the distal jejunum and ileum, but not in the appendix vermiformis, the caecum, or the hindgut, despite the large number of neuroendocrine cells present in this area. In addition, sst2A cells were found in the whole gastrointestinal tract in the myenteric and submucosal plexus. Conclusions: While sst2A receptors on antral gastrin cells presumably mediate somatostatin inhibition of gastrin secretion, the effects of somatostatin on motility and ion transport in the lower gastrointestinal tract may be mediated by sst2A receptors in the neural plexus. These data provide a molecular basis for the physiological actions of somatostatin in human gastrointestinal tissue.